O foco oblíquo da memória: uma questão de autoria em Lobo Antunes_ - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Literature as an artistic manifestation has been exploring the human soul in ways over time. Being a representation of the author’s view of life, questions about the authorship of literature span the centuries, fueling all sorts of critical and theoretical discussions. António Lobo Antunes, writer, psychiatrist and ex-soldier, develops a plot with a strong autobiographical content in his novel. In the light of the narration of memoirs, we find in the first Antunean trilogy, composed by Memória de Elefante, The Land at the End of the World and Knowledge of Hell, fragmented dimensions of a protagonist who is his alter ego, sewing the diegetic universe to the level of the reality of the Colonial War and its impacts on the returned man. Supported by several studies that focused on the theme of authorship, this dissertation seeks to understand the relationship between author and work, exploring the limits and effects of reading these autobiographical novels. Making use of discussions about author, intentionality and reality x fiction, the discussion dialogues with critics, theorists and novelists who were established as authorities in these subjects, such as Roland Barthes, Michel Foucault, Antoine Compagnon, Umberto Eco and Orhan Pamuk, in addition to others scholars who make up the range of experts on these topics.
Keywords: António Lobo Antunes; Autoria; Memória; Romance autobiográfico; António Lobo Antunes; Authorship; Memory; Autobiographical novel; CNPQ::LINGUISTICA, LETRAS E ARTES